Quem quer fazer arte? Pelos playgrounds das salas de aula - Duek, Paulo Saul (2020)
The present research was guided by the following question: if in contemporary school Art is placed as a curricular component that should break barriers and point to new paths, even because it is precisely Art, why is it so often possible to witness a significant neglect arising from of the student to allow himself to be an actor in this proposal and of a teacher who has little interest in meaningful teaching performance? Now, if the importance and the valuation given by the teachers themselves, in terms of Art and Education, interfere in their practices, the same happens when there is an excess of value also to neglect, resulting in the absence of a pulsation of life than teaching, especially when you want to be an educator, you demand it. Thus, by paying attention, among other factors, to the insufficient workload dedicated to the Art component and the absence of links that may result from it, in addition to the feeling of being trapped in the established curriculum content, this research allowed us, in addition to seeking possible answers, also follow teaching practices and collect testimonies, in addition to experiencing the field experience, in what we call “playgrounds” in the classroom. The research universe was a municipal public school of Elementary Education II in the city of Praia Grande, on the coast of São Paulo. To support the research, we rely mainly on the philosopher Gilles Deleuze and the actor, poet and thinker Antonin Artaud, who deal, among others, with dense questions of life and its absence, but especially of its permanence in becoming.